A multi-criteria assessment of the production and marketing systems of local mountain food. Issue 4 (December 2014) - Prišenk, Jernej; Rozman, Črtomir; Pažek, Karmen; Turk, Jernej; Bohak, Zarja; Borec, Andreja
Abstract A multi-criteria model for a qualitative assessment of the production and marketing of local food products (LFP) from mountain areas has been developed by applying the DEX method. The development of the model was carried out and finally applied to ten local food products. The results were given in the form of a qualitative final assessment of both the production and marketing phases. By applying a plus–minus-1 analysis, the influence of various attributes on the final assessment of the LFP was examined. The main bottlenecks in the production and marketing processes were found. A sensitivity test was used to explain the influence of production and marketing on the final assessment. The results give clear directions as to which of the main attributes must be changed/improved or further developed to enable the successful promotion of local food products, which would give rise to an improved economy in mountain areas.